Education and Enterprise Empowerment: The Mediating Role of Digital Skills among Indonesian Micro- Small Entrepreneurs - Afif Zaerofi; Aminah Nuriyah; Shofi Arofatul Marits; Abdullah Haidar (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2026)
Objective: Education and digital skills are increasingly recognized as key resources for strengthening entrepreneurial capacity and business sustainability. This study examines the influence of education on Micro- Small Entrepreneurs empowerment and investigates the mediating role of digital skills among micro-small entrepreneurs in Indonesia. Method: This study employed a quantitative approach using Structural Equation Modelling Partial Least Squares (SEM-PLS). Data were collected from 108 valid micro-small entrepreneurs operating in the food, fashion, and retail sectors across West Java Province, Indonesia. The proposed model assessed the relationships among education, digital skills, and Micro- Small Entrepreneurs empowerment. Results: The results indicate that education has a positive and significant effect on digital skills and Micro- Small Entrepreneurs empowerment. Digital skills also significantly enhance Micro- Small Entrepreneurs' empowerment. Furthermore, digital skills partially mediate the relationship between education and Micro- Small Entrepreneurs empowerment, suggesting that educational attainment contributes to entrepreneurial empowerment both directly and indirectly through improved digital capabilities. Implications: The findings highlight the importance of strengthening entrepreneurship education and digital literacy programs to foster inclusive and sustainable Micro- Small Entrepreneurs development. Policymakers, educational institutions, and development agencies should prioritize initiatives that simultaneously enhance educational attainment and digital competencies among micro-entrepreneurs. Originality or Novelty: This study extends the Micro- Small Entrepreneurs empowerment literature by integrating education and digital skills within a single analytical framework and empirically demonstrating the mediating role of digital skills in explaining how education translates into entrepreneurial empowerment among Indonesian micro-small enterprises.